Endophytic fungi and their compounds of agronomic interest - Ferreira, Tatiani Pereira de Souza; Ferreira, Talita Pereira de Souza; Mourão, Dalmarcia de Souza Carlos; Xavier, Michelle da Cunha Abreu; Marques, Gessyk Monteiro; Lima, Lorena Ribeiro; Tavares, Elsiane do Socorro Pinheiro; Ribeiro , Stefanne da Silva Cabral; Chapla, Vanessa Mara; Santos, Gil Rodrigues dos (Seven Editora, 2023)
INTRODUCTION: Endophytic fungi are microorganisms that live inside plants for at least part of their life cycle without causing any harm. They can stimulate dormancy breakdown by producing metabolites that act on the embryo that stimulate seed germination and potentially growth promoters with symbiotic interactions between plants. The compounds produced have diverse effects, such as: stimulators of growth and development of plants, increased mineralization and availability of nutrients, producing stimulating compounds releasing phytohormones and breakdown of dormancy. MATERIAL AND METHODS: Selected several articles that were collected in the scientific databases in Portuguese and English. RESULTS AND DISCUSSION: Articles were selected for the elaboration of a table reporting the main compounds in the promotion of growth and breakdown of dormancy. CONCLUSION: Endophytes can contribute to the discovery of new biomolecules for various biotechnological applications and the development of sustainable agriculture. DOI:https://doi.org/10.56238/alookdevelopv1-174